Experimental model of venous catheters central feeding in rats - Valiñas, Roberto; Méndez, Estela; Miegge, Laura; Scaniello, Varinia; Etcheverría, José Pedro; Ferreiro, Gustavo; Bertullo, Hugo (Cirugía del Uruguay, 1994)
A prospectiva study which analyses an experimental model of central venous viae in rats was carried out. Technique, complications, and applicability is analysed; a difference is found when considering complications as compared to papers of previous authors, and it is concluded that the technique is acceptable far short term experiences where it is necessary to employ central venous accesses.